2010
DOI: 10.1186/1756-0500-3-38
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the wild type loxP site in BACs from the public domain with lox66 using a lox66 transposon

Abstract: BackgroundChromatin adjoining the site of integration of a transgene affects expression and renders comparisons of closely related transgenes, such as those derived from a BAC deletion series retrofitted with enhancer-traps, unreliable. Gene targeting to a pre-determined site on the chromosome is likely to alleviate the problem.FindingsA general procedure to replace the loxP site located at one end of genomic DNA inserts in BACs with lox66 is described. Truncating insert DNA from the loxP end with a Tn10 trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…For example, cross recombination between loxP and lox511 has been reported to occur at efficiencies ranging from 5 to 100 % under those experimental conditions that express Cre constitutively (33,(35)(36)(37)(38). We have not observed such cross-recombination, and high levels of stringency in vivo in recombining identical lox sites (21,24), or lox sites with at least identical spacers (39), have been achieved with Cre protein expressed from its native source namely, a phage P1 infection (21,24,39). Depending on whether a loxP or a lox511 transposon is used, truncations from the corresponding lox-end can be made readily and exclusively with high stringency [shown schematically in Figure 4].…”
Section: Potential Cre-mediated Cross-recombination Of Loxp and Lox511 mentioning
confidence: 55%
“…For example, cross recombination between loxP and lox511 has been reported to occur at efficiencies ranging from 5 to 100 % under those experimental conditions that express Cre constitutively (33,(35)(36)(37)(38). We have not observed such cross-recombination, and high levels of stringency in vivo in recombining identical lox sites (21,24), or lox sites with at least identical spacers (39), have been achieved with Cre protein expressed from its native source namely, a phage P1 infection (21,24,39). Depending on whether a loxP or a lox511 transposon is used, truncations from the corresponding lox-end can be made readily and exclusively with high stringency [shown schematically in Figure 4].…”
Section: Potential Cre-mediated Cross-recombination Of Loxp and Lox511 mentioning
confidence: 55%
“…Previous studies had reported recombination between loxP and lox511 to occur at efficiencies ranging from 5 to 100% under experimental conditions that express Cre constitutively [54][55][56][57][58][59]. Such cross-recombination was not observed when Cre protein was expressed in a phage P1 infection in vivo [49,60,61], and high levels of stringency in recombining identical lox sites [49,60], or lox sites with at least identical spacers was achieved [61]. Truncations of genomic DNA in a BAC from either end are not only efficient, but are specific for that end.…”
Section: Cross-recombination Between Loxp and Lox511 Sites Does Not Occmentioning
confidence: 88%
“…Previous studies had reported recombination between loxP and lox511 to occur at efficiencies ranging from 5 to 100% under experimental conditions that express Cre constitutively [70][71][72][73][74][75]. Such cross-recombination was not observed when Cre protein was expressed in a phage P1 infection in vivo [65,76,77], and high levels of stringency in recombining identical lox sites [65,76], or lox sites with at least identical spacers was achieved [77]. Truncations of genomic DNA in a BAC from either end are not only efficient, but are highly specific for that end.…”
Section: Cross-recombination Between Loxp and Lox511 Sites Does Not Omentioning
confidence: 88%